P201 Health literacy and sleep apnoea. (16th November 2010) - Ghiassi, R; Partridge, M R
Abstract : Introduction: We have previously demonstrated that 33% of new patients and 16% of serial users have difficulty completing the Epworth Sleepiness Scale (ESS). To explore reasons for this we assessed literacy in a further group of patients. Methods: 122 Sleep Centre and Lung Function laboratory patients were approached and assessed for level of functional literacy in medicine using the REALM questionnaire. A score ≤60 suggests a literacy level that would struggle with patient education materials and prescription labels. Education and English language data were collected. Results: 86/92 (93.3%) Sleep and 30/30 (100%) Lung function (LF) patients completed REALM. 5 (5.6%) in the Sleep group declined when shown the test. One did not complete due to time restrictions. Mean age was 51.2 ± 11.8 years Sleep and 56.1 ± 17 years LF. Mean age leaving formal education was 18.7 ± 2.9 years Sleep and 17.7 ± 2.9 years LF. In the Sleep cohort 24% (21/86) had a graduate and 15% (13/86) postgraduate education vs. LF 27% (8/30) graduate and 3% (1/30) postgraduate education. REALM scores are shown in Abstract P201 Table 1 grouped into the standard four ranges. 78% (Sleep) and 83% (LF) spoke English as their mother tongue; all patients used English as their everyday spoken language. Conclusions: Assessing literacy in patients is not easy. We have previously shown how patients struggle to complete the ESS. Problems completing forms occur for many reasons and evidence suggests that clinicians overestimate patient literacy. We found evidence of impaired health literacy in 16.3% of Sleep and 10% of Lung function patients. That some Sleep patients declined to be tested once shown the questionnaire might suggest the 16.3% score is underestimated. Why Sleep patients should fare worse than LF patients is unclear especially when university and age leaving education were higher in the sleep cohort. All used English as their everyday language however fewer Sleep patients had English as their mother tongue. Cognitive deficits associated with undiagnosed obstructive sleep apnoea syndrome and increased sleepiness could conceivably be a contributory factor. This study suggests clinicians need to provide clinical material and information in a format that is comprehensible to a wide range of patients (such as pictorial format) and that Sleep patients may have special needs.